BEGAL-PERILAKU MENYIMPANG MASYARAKAT YANG DILAKUKAN OLEH REMAJA (Studi Kasus tentang Begal-Perilaku Menyimpang Masyarakat, Yang Dilakukan Oleh Remaja, di Kota Sorong, Papua Barat) - Virginia Leuwol, Natasya; Uktolseja, Lulu Jola (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The increasing crime rates of violent motorcycle theft, especially by teenagers, is no longer a juvenile delinquency, but a juvenile crime. This paper will evaluates cases of violent motorcycle theft by teenager and identifies the cause by juvenile delinquency theories. By comparing the cases using 10 causes of juvenile delinquency shifting into juvenile crime by United Nation. As the result, I found that adolescent’s transition without self-acceptance; behavior reinforcement and social support system let them into sadistic criminal. Thus, the development system should be corrected to focus on adolescent’s psychological welfare.